2021
DOI: 10.12775/jehs.2021.11.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Immediate effects of Ukrainian phytocomposition on biophotonics (GDV), EEG and HRV parameters

Abstract: Background. Back in 2015, we registered short-term reactions to the Ukrainian phytocomposition of electroencephalogram and heart rate variability parameters. At the same time, we also recorded the reactions of biophotonics (GDV) parameters, but due to the skepticism of Ukrainian academic science regarding this method, we did not dare to include the results in the article. Materials and methods. The object of observation were 12 women (44±13 years) and 62 men (44±12 years) with dysfunction of neuro-endocrine-im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Taking into account literature data on the direct neurotropic effect of phytoadaptogens in vitro and in vivo [26], previously published data on changes in EEG&HRV parameters as well as relationships between EEG and HRV, EEG&HRV and adaptogene hormones, EEG&HRV and immunity parameters [5][6][7] [9][20] [23], the neurogenic mechanism of the revealed effects of balneotherapy factors seems to be very real.…”
Section: Scatterplot Of Canonical Correlation Between the Changes In ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account literature data on the direct neurotropic effect of phytoadaptogens in vitro and in vivo [26], previously published data on changes in EEG&HRV parameters as well as relationships between EEG and HRV, EEG&HRV and adaptogene hormones, EEG&HRV and immunity parameters [5][6][7] [9][20] [23], the neurogenic mechanism of the revealed effects of balneotherapy factors seems to be very real.…”
Section: Scatterplot Of Canonical Correlation Between the Changes In ...mentioning
confidence: 99%
“…We have previously explored effects of phytocomposition "Balm Truskavets'", which is analogous to the "Balm Kryms'kyi", on parameters of neuro-endocrine-immune complex and biophotonics in humans with maladaptation [6][7] [9] [32].…”
Section: Introductionmentioning
confidence: 99%
“…An even stronger proof of the adaptogenic ability of the phytocomposition is an increase in the leukocytary Popovych's adaptation index [15] (sorry for the immodesty, but it is necessary not to be confused with the leukocytary Garkavi's adaptation index [20]), which reflects the quantitative assessment of qualitative changes in the body's general adaptive reactions, namely, a decrease in the share of pathological and premorbid (disharmonious) reactions and an increase in the share of normal (harmonious) reactions [19,21,30,47]. The adaptogenic effect of phytocompositions is accompanied by favorable changes in the parameters of neuro-endocrine regulation, as well as acupuncture points and bioelectrophotonics [15][16][17][18]51].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier we showed that the Ukrainian phytocomposition "Balm Truskavets'" (ТУ У 15.8-24055046-005:2009, produced by private research-production enterprise "Ukrainian Balms", Mykolaїv, Ukraine; is analogous to the previous "Balm Kryms'kyi" [1,18,25,26,33,42,47]) exerts immediate (in 1,5 hours after use) modulating effects on parameters of EEG and HRV as well as biophotonics (kirlianogram, gas discharge visualization, GDV) [16,55]. This gives grounds for finding out the long-term (course) effects of the phytocomposition on these parameters.…”
Section: Introductionmentioning
confidence: 99%